PENGEMBANGAN VIDEO PEMBELAJARAN BERBANTUAN RENDERFOREST PADA MATA PELAJARAN IPS KELAS VII DI UPT SMPN 5 PANCA RIJANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to create learning videos with the help of the Renderforest application on Social Sciences (IPS) subjects for class VII at UPT SMPN 5 Panca Rijang and to test the level of validity, practicality, and effectiveness of the videos. The research method applied is Research and Development (R&D) using the ADDIE development model which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included material and media expert validators, IPS teachers, and 35 class VII students. The validation results showed that the learning videos were very valid with scores of 87% (media experts) and 86% (material experts) respectively. The practicality test showed very practical results with an average percentage of 84%, while the effectiveness test through a comparison of pretest and posttest scores showed a significant increase with the N-Gain value in the effective category. Therefore, learning videos supported by Renderforest are suitable for use as learning tools to deepen students' understanding in IPS.